Improved low-temperature catalytic oxidation performance of Pt-based catalysts by modulating the electronic and size effects. (11th June 2020) - Liang, Yanli; Ding, Xinmei; Wang, Jianli; Zhao, Ming; Dan, Yi; Jiang, Long; Chen, Yaoqiang
Abstract : The electronic effect between PVA and platinum could be modulated though reaction time, restraining the chain movement and affecting the platinum dispersion, both of which closely affects the low-temperature performance of the Pt-based catalyst. Abstract : Polyvinyl alcohol (PVA) has been shown to interact with platinum ions by manipulating the reaction time. It was interestingly found that the improved low-temperature oxidation performance of Pt-based catalysts in promoting the conversion of CO/C3 H6 /NO was mainly contributed to by a higher content of metallic platinum species, accompanied by relatively smaller platinum nanoparticle size. Besides, DTA and in situ DRIFTs of the un-roasted catalysts showed that an appropriate reaction time (10 h) between the platinum ions and polyvinyl alcohol resulted in a strong electronic intensity of the platinum. Both these factors led to a greater formation of formate species and the lowest light-off temperature of CO (176 °C), C3 H6 (187 °C), and NO (214 °C). This simple method involving tuning the interaction of polymer and metal ions would be positive for optimizing the electronic state and size efffect of metals in catalysis.